2015
DOI: 10.1089/jmf.2014.0121
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Effect of a Blue-Green Alga (Nostoc commune) Is Attributed to Its Nonlipid Fraction by Decreasing Intestinal Cholesterol Absorption in C57BL/6J Mice

Abstract: We previously demonstrated that Nostoc commune var. sphaeroids Kützing (NO), a blue-green alga (BGA), exerts a hypolipidemic effect in vivo and its lipid extract regulates the expression of genes involved in cholesterol and lipid metabolism in vitro. The objective of this study was to investigate whether the hypolipidemic effect of NO is attributed to an algal lipid or a delipidated fraction in vivo compared with Spirulina platensis (SP). Male C57BL/6J mice were fed an AIN-93M diet containing 2.5% or 5% of BGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Then, after 4 weeks of HFD, the mice received an HFD supplemented with NO (2.5%), NO (7.5%), or without NO for 6 weeks. This study shows that supplementing diet with NO significantly reduces TC, TG, and LDL, and increases HDL in serum (Table 4), which is consistent with a previous study finding that NO treatment significantly lowered plasma lipid (18). Although the serum lipid levels have not reached the control levels, it still shows that NO exerts a positive effect towards ameliorating lipids and has the potential to prevent hyperlipidemia in mice.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Then, after 4 weeks of HFD, the mice received an HFD supplemented with NO (2.5%), NO (7.5%), or without NO for 6 weeks. This study shows that supplementing diet with NO significantly reduces TC, TG, and LDL, and increases HDL in serum (Table 4), which is consistent with a previous study finding that NO treatment significantly lowered plasma lipid (18). Although the serum lipid levels have not reached the control levels, it still shows that NO exerts a positive effect towards ameliorating lipids and has the potential to prevent hyperlipidemia in mice.…”
Section: Discussionsupporting
confidence: 91%
“…They also have bioactive properties, such as antiviral, antitumor, antidiabetic, anti-inflammatory, and lipid-modulating effects (15,16). Previous studies have shown that NO and its extracts significantly reduced plasma total cholesterol (TC) and triglyceride (TG) levels in male C57BL/6j mice and may have the potential to reduce the risk of atherosclerosis (16)(17)(18). Nevertheless, it remains unknown whether NO could have any effect on body weight or regulatory effects on liver lipid accumulation.…”
mentioning
confidence: 99%
“…N. sphaeroides Kütz, also known as Ge‐Xian‐Mi in China, has been used as a health product for centuries (Hao et al, 2011; Ku et al, 2013). N. sphaeroides Kütz is high in polysaccharide, amino acid, protein, vitamin, and mineral contents (Yang et al, 2011), and has bioactive properties, including antiviral, antitumor, antidiabetic, anti‐inflammatory, and lipid‐modulating activities (Ku, Kim, Pham, Yang, Wegner, et al, 2015; Ku, Kim, Pham, Yang, Weller, et al, 2015; Ku et al, 2013). Previous studies have shown that N. sphaeroides Kütz and its extracts significantly reduced plasma TC and TG levels in male C57BL/6j mice and may reduce atherosclerosis risk (Ku, Kim, Pham, Yang, Weller, et al, 2015; Yang, Kim, Park, & Lee, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Pravastatin (PR) treatment reduced duodenal cholesterol transporter expression in mice. PR-induced increases in liver X receptor may be involved in reduction of Niemann-Pick C1-like 1 expression, lowers the intestinal cholesterol absorption [33].…”
Section: Physiological Factors Affecting Cholesterol Absorption In Inmentioning
confidence: 99%
“…Further studies reveal that Anacetrapib (ANA) promotes pre β High Density Lipoprotein in vivo functionality, but has no effects on absorption of cholesterol [37]. Another study showed that the nonlipid fraction of Nostoc commune var.…”
Section: Physiological Factors Affecting Cholesterol Absorption In Inmentioning
confidence: 99%